2021
DOI: 10.1037/pag0000633
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in intuitive moral decision-making: Associations with inter-network neural connectivity.

Abstract: Positions of power involving moral decision-making are often held by older adults (OAs). However, little is known about age differences in moral decision-making and the intrinsic organization of the aging brain. In this study, younger adults (YAs; n = 117, M age = 22.11) and OAs (n = 82, M age = 67.54) made decisions in hypothetical moral dilemmas and completed resting-state multi-echo functional magnetic resonance imaging (fMRI) scans. Relative to YAs, OAs were more likely to endorse deontological decisions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 132 publications
(199 reference statements)
0
10
0
Order By: Relevance
“…The approach has proven to be highly reliable for precision mapping 13 . Subsets of the data described here have provided novel insight into inter-regional BOLD signal variability properties in young adults 14 , and into large-scale network configuration differences between younger and older adults related to semantic autobiographical memory 15 and moral cognition 16 . Despite the demonstrable advantages of ME-fMRI data and processing, there is currently a paucity of ME-fMRI data available in open access repositories (for task and naturalistic viewing exceptions, see 17 , 18 ).…”
Section: Background and Summarymentioning
confidence: 99%
“…The approach has proven to be highly reliable for precision mapping 13 . Subsets of the data described here have provided novel insight into inter-regional BOLD signal variability properties in young adults 14 , and into large-scale network configuration differences between younger and older adults related to semantic autobiographical memory 15 and moral cognition 16 . Despite the demonstrable advantages of ME-fMRI data and processing, there is currently a paucity of ME-fMRI data available in open access repositories (for task and naturalistic viewing exceptions, see 17 , 18 ).…”
Section: Background and Summarymentioning
confidence: 99%
“…A study done by Huang S. et al [21] showed that older adults, compared to younger adults, made more deontological decisions in DI dilemmas but did not differ from younger adults in UI dilemmas. Older adults are less likely to support instrumental injury or sacrifice maximal collective utility, especially if that support is intuitively compelling.…”
Section: Theory Of Decision Makingmentioning
confidence: 98%
“…Previous work has shown that older adults, who generate less detailed episodic representations than younger adults (Addis et al, 2008), also experience greater negative affect in response to sacrificial utilitarian decisions (McNair et al, 2019). This negative affect is associated with a tendency for older adults to rate a utilitarian decision as less acceptable than younger adults (McNair et al, 2019), particularly when the utilitarian decision is likely to generate an aversive emotional response (e.g., as in the trolley dilemma; Huang et al, 2021).…”
Section: Episodic Models Of Moral Dilemmasmentioning
confidence: 99%
“…The traditional dual-process model, which maps deontological judgments onto rapid, intuitive “System 1” processes and utilitarian judgments onto controlled, deliberative “System 2” processes (Greene, 2014; Greene & Haidt, 2002), predicts that stress will facilitate rapid, emotional, deontological judgments. Although this prediction has received some empirical support (e.g., Youssef et al, 2012), recent work has called into question the mapping of System 1 versus 2 processes onto deontological and utilitarian judgments, respectively (Bago & DeNeys, 2019; Huang et al, 2021). Bago and DeNeys (2019) found that the majority of participants who gave a utilitarian response when given time to deliberate had previously provided a utilitarian response when under time pressure and cognitive load.…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%